Ethics In The Information Technology Process : A Case Study Of Social Media - Womboiang, Felni Gemma Nucifera; JMJ, Sr Youla Agnes Lontaan; Lengkong, Gledys Tirsa (Journal of Scientific Insights, 2024)
Technological developments cannot be avoided with life, surely we do not just sit back and miss the development of the world. Keeping up with information technology actually makes it easier to obtain information or even to benefit mankind. Easiest way to communicate now is by using social media. Ethics applies not only to real life but also to the development of information technology with its broad array of ethical applications. On the basis of freedom of opinion, people feel that it is their personal right to share potentially inappropriate tips. Although the Electronic Information and Transactions, it is felt that it would have no effect on ordinary people. This has proved to be with the pervading of social media in slander, confrontation, bullying, abusive speech, or even vulgarity. The study uses case study methods on social media applications, noting how upload which is still very freely accessible to others may even trigger big problems to the legal realm. The policy and maturity of the account owner or individual individual is to be expected, so that how the upload is made may be useful and impact information for everyone who sees it regardless of age.